Tafsir Nuzuli Karya Ulama Nusantara: - Fikri, Khairul (SUHUF, 2022)
This article analyzes the Tafsir Sinar by an Indonesian’s ‘ulama’ from West Sumatra named Abdul Malik Ahmad (1912-1993). Tafsir Sinar is a book of interpretation that is different from the works of his contemporaries, such as Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Mishbah by Quraish Shihab, because it is compiled with tartib nuzuliy surah. Using library research and a descriptive-analytical approach, this article analyzes the writing background, characteristics or methodology, and Malik Ahmad’s interpretation in Tafsir Sinar. This study found that the purpose of Malik Ahmad wrote his commentary is to make the spirit of the Qur'an is understood as it was when it was revealed in the early days. By applying a coherent systematic presentation with detailed explanations in his commentary, Malik Ahmad combines the informations from several riwayah with his thoughts, and refers to other interpretations as reinforcement. The style of language used is reportage style and its not bound by the rules of scientific writing. In the process of interpretation, he also performs fragmentation by dividing a surah into several groups of verses, then explaining the munasabah between the groups of verses.